The Integration of Compiled and Explicit Causal Knowledge for Diagnostic Reasoning - Senyk, Oksana (1988)
Causal reasoning gained prominence in the “second generation” of artificial intelligence in medicine (AIM) programs in the late 1970s. Today we face the challenge of developing methods of compiled causal reasoning which approximates the clinical reasoning employed by expert diagnosticians for the efficient solution of most cases. To this end, we have developed the compiled causal link technique, by means of which a diagnostic system can solve routine cases quickly and can deal efficiently with overlapping disease manifestations due to interaction among multiple co-occurring disorders [6]. In this paper we address the issue of integrating this compiled causal reasoning with an explicit causal model of the underlying pathophysiological mechanisms. The explicit causal model is needed not only to support explanation, but also as a fail-safe for handling the cases which prove to be too complex for the compiled model.